Growth Center Identification and Accessibility-Based Spatial Interaction in Bondowoso Regency - Indah Ludiana Putri; Bambang Juanda; Mangasa Augustinus Sipahutar (Department of Urban and Regional Planning, Universitas Diponegoro, 2025)
Bondowoso Regency, as a developing rural and semi-urban area, faces dynamic development challenges, particularly inter-district development disparities and uneven concentrations of economic activity. This inequality reflects a disparity between districts in terms of facilities, accessibility, and the distribution of economic activity centers. The determination of growth centers is a crucial strategy for identifying areas with the potential to be drivers of development. This study aimed to determine the growth center and the accessibility-based spatial interaction in Bondowoso Regency, East Java, Indonesia. The methods used for this study were scalogram, gravity, and overlay analysis. The results showed that Bondowoso District has 561 facility units with a regional development index value of 69.86 (Hierarchy I). This indicates its role as a growth center that can influence the strength of spatial interactions between districts in Bondowoso Regency. The highest spatial interaction value was found in Tenggarang District at 39,708, while the lowest was in Sukosari District at 3,980. The optimization of these central places is expected to create a polarization effect and increase the attractiveness of the surrounding areas. This can be a consideration for the Bondowoso Regency government in determining the direction of development to reduce inter-regional inequality.